Kansas women - Hill, Grace Edna (My University, 1899)
Introduction: The history of the Women of Kansas is so interwoven with the history of the state that it is almost impossible to tell their story without giving a part as the whole of the history of Kansas. It would take the inspiration of a poet, the eloquence of an orator, and the genius of a writer, to do justice to their sterling worth, their ambition and their endurance. Characters were developed, grand and noble, which exerted their influence in the years that followed, they deprived themselves of the comforts of life, and deemed no sacrifice too great which gave them the opportunity of educating their children. In the state today no truer, braver men and women ever lived, and it is this kind who has made an impress upon Kansas and her institutions. What Kansas is today, she owes to the foundations laid by her brave pioneers. Kansas has an eager restless spirit and her people are ever progressing. This spirit is manifested in the service of women as county superintendents, regents and professors of colleges, organizers of clubs in literary and art circles, in the industrial world and in almost every other line which could be mentioned.
Citation: Hill, Grace Edna. Kansas women. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Women as Wage-Earners; Women as Political Leaders; Women as Writers; Theses; Manuscripts (documents)